Hypercholesterolemia - non-pharmacological treatment, monotherapy or combination therapy. Review of the literature - Weronika Łowicka; Magdalena Graca; Anna Szeliga; Agata Szostak; Karolina Korta; Karolina Oluszczak; Kinga Szopińska; Liliana Dyląg; Maria Janina Śmigielska-Mikołajczyk; Konrad Wawszkowicz (Nicolaus Copernicus University in Toruń, 2024)
Introduction: As the number of scientific studies on lipid metabolism disorders increases, awareness among the medical community and the general population about the impact of hypercholesterolemia on the risk of cardiovascular diseases is growing. Elevated cholesterol levels in the blood are a major factor in the development of atherosclerosis, thereby increasing the likelihood of sudden cardiovascular events such as heart attacks or strokes. Maintaining normal cholesterol levels in the blood requires effective collaboration between the doctor and the patient, combining optimal pharmacotherapy with effective non-pharmacological methods based on the introduction of a balanced diet and moderate, regular physical activity. Current guidelines, based on numerous scientific studies, provide a clear framework for lipid-lowering treatment, with statins being an integral part. In cases where monotherapy is ineffective, ezetimibe and monoclonal antibodies, among others, can be used. In our work, we will discuss the possibilities of both non-pharmacological therapy and pharmacotherapy.   Aim of the study: The aim of this study is to review current knowledge on non-pharmacological and pharmacological therapy in hypercholesterolemia.    Material and method: This article presents the current state of knowledge about non-pharmacological and pharmacological therapy in hypercholesterolemia. Publications reviewed using the PubMed platform contain recent report in field of lipid metabolism disorders. The search included the keywords: ,Hypercholesterolemia', ,LDL-C', ,Statin', ,Ezetimibe',    ,PCSK9 inhibitors'.